Digital Inequality In The Archipelago: A Deep Divide Into Balikpapan’s Mobile Banking Ecosystem - Benita Bhanuwati Ardi; Refi Rifaldi Windya Giri (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Indonesia, archipelagic nation with a growing need for digitalization, has cities such as Balikpapan leading the way in mobile banking as part of this digital transformation. Balikpapan's journey is hindered by a digital divide caused mainly by unequal internet distribution. This research focuses on evaluating the impact of motivation, tangible access, and proficiency in mobile banking on its adoption. The study also examines the influence of demographic variables such as education, age, gender, and location on this phenomenon. The digital divide continues to be a global concern, exhibiting different forms in different regions, as supported by previous research. Balikpapan's urban trajectory offers a unique context for reevaluating this divide. A sample of 347 Balikpapan residents was analyzed using WarpPLS 7.0 software, applying SEM-PLS criteria. The findings reveal a minimal digital divide in the adoption of mobile banking. Disparities in education and location are apparent. This study builds upon the work of van Deursen & van Dijk (2019) and offers new perspectives on the evolving focus from digital access to a more comprehensive development of digital skills. The significance of Balikpapan's narrative lies in its demonstration of the power of intrinsic motivation in driving digital adoption. This highlights the need to reassess strategies aimed at achieving comprehensive digital inclusion.